2004
DOI: 10.1021/jm030483s
|View full text |Cite
|
Sign up to set email alerts
|

NR2B-Selective N-Methyl-d-aspartate Antagonists:  Synthesis and Evaluation of 5-Substituted Benzimidazoles

Abstract: Two classes of 5-substituted benzimidazoles were identified as potent antagonists of the NR2B subtype of the N-methyl-d-aspartate (NMDA) receptor. Selected compounds show very good selectivity versus the NR2A, NR2C, and NR2D subtypes of the NMDA receptor as well as versus hERG-channel activity and alpha(1)-adrenergic binding. Benzimidazole 37a shows excellent activity in the carrageenan-induced mechanical hyperalgesia assay in rats as well as good pharmacokinetic behavior in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 21 publications
4
46
0
Order By: Relevance
“…Similar to Zn 2ϩ binding to the ATD of GluN2A (see section VI.E), ifenprodil increases the potency of proton inhibition of NMDA receptors Mott et al, 1998). Rich pharmacology exists for this site, with nearly a dozen structural classes described, including oxamides (Barta-Szalai et al, 2004), 4-(3,4-dihydro-1H-isoquinolin-2-yl)-quinolines (Bü ttelmann et al, 2003), benzamidines (Claiborne et al, 2003), 5-substituted benzimidazoles (McCauley et al, 2004), indole-2-carboxamides (Borza et al, 2006(Borza et al, , 2007, benzyl cinnamamidines (Tamiz et al, 1999;Curtis et al, 2003), and other biaryl analogs (Tamiz et al, 1998;Wright et al, 2000;Tahirovic et al, 2008;Mosley et al, 2009). …”
Section: E Noncompetitive Antagonistsmentioning
confidence: 99%
“…Similar to Zn 2ϩ binding to the ATD of GluN2A (see section VI.E), ifenprodil increases the potency of proton inhibition of NMDA receptors Mott et al, 1998). Rich pharmacology exists for this site, with nearly a dozen structural classes described, including oxamides (Barta-Szalai et al, 2004), 4-(3,4-dihydro-1H-isoquinolin-2-yl)-quinolines (Bü ttelmann et al, 2003), benzamidines (Claiborne et al, 2003), 5-substituted benzimidazoles (McCauley et al, 2004), indole-2-carboxamides (Borza et al, 2006(Borza et al, , 2007, benzyl cinnamamidines (Tamiz et al, 1999;Curtis et al, 2003), and other biaryl analogs (Tamiz et al, 1998;Wright et al, 2000;Tahirovic et al, 2008;Mosley et al, 2009). …”
Section: E Noncompetitive Antagonistsmentioning
confidence: 99%
“…3). Some of the most effective substitutions of the B ring among ifenprodil analogs have been 5-hydroxy-benzimidazole, para-N-phenylmethanesulfonamide, benzoxazolinone, and benzimidazolinone (Wright et al, 2000;Nagy et al, 2003;Barta-Szalai et al, 2004;McCauley et al, 2004;Tahirovic et al, 2008;Mony et al, 2009a;Mosley et al, 2009). Docking compounds with different B-ring moieties showed that the hydroxyl-containing groups exhibited a pose similar to ifenprodil and Ro 25-6981, forming hydrogen bonds with Glu236 and a water molecule (Figs.…”
Section: Glun2b-selective Allosteric Modulator Binding 349mentioning
confidence: 99%
“…Based on the previous structure-activity relationship studies, [20][21][22] the SPECT imaging agent candidates 8, 9, and 13 were designed, in which an iodine atom was introduced into the 4'-position (R 2 -position) of benzyl-or phenoxy-piperidine group of benzimidazoles. Lead compound 1a was synthesized according to the literature.…”
Section: Chemistrymentioning
confidence: 99%
“…Recently, a new series of benzimidazole derivatives 1 and 2 are developed as novel NR2B antagonists (Fig. 2), 20 which have similar chemical structures with EMD-95885. For example, compound 1a showed excellent affinity for the NR2B subunit (Ki= 1.5 nM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation